Pomoč z umetnostjo osebi po hudi poškodbi glave - Kokalj, Ines (Socialno delo, 2017)
The article is based on the personal experience of a volunteer working in Plus5, an association for help with art. The volunteer had been helping an individual who had to live with the consequences of a severe head injury. After the eighteen-month period of intervention, particularly through creative art expression (especially creative individual and group art activities), all the members of a group who had been actively involved in the research, perceived positive effects of the interventions on the user: improved concentration (and therefore better left hand control), more efficient expression of feelings and improved self-esteem. The results of the research confirmed the working hypothesis that the use of different methods and techniques of help with creative art expression will have a beneficial impact on the user's concentration, emotional expression and self-image.
Keywords: social work; socialno delo; poškodbe glave; rehabilitacija; vocational rehabilitation; likovno izražanje; čustva; samopodoba